The Academic Office: Constitutive Entanglement and Organizational Matter - Ruth, Damian (Organizational Aesthetics, 2015)
This paper explores how a group of academics arranged and decorated their offices, revealing qualities of academic life of which academics are not usually conscious, such as the connectivity between academics, and the connectivity between practice and artifacts. The research confirms the importance of the sensory and aesthetic dimensions of organizational life, of artifacts and place and demonstrates the sociomateriality of academic practice. The research took advantage of a situation where academics in the author’s university were given some latitude on how they wanted to arrange their renovated offices. Interviews with colleagues revealed that the way they had (or had not) arranged, decorated and furbished their offices offered a rich source of data about their sense of place, purpose, practice and identity. Many of the things in these offices were embodied metaphors infused with meaning. Responses illustrated the way in which the office of an academic is a temporary construction site of relationships expressed through artifacts to which are delegated many profound tasks and responsibilities. It is a site where, through the material expression of self, that self and its work are theorized and the theories are materialized. Examining the aesthetic and materiality of the academic office illuminates how it is a prime site of âconstitutive entanglementâ and how the organization is constantly disassembled and reassembled.